Catechizing at Home, 1740–1870: Instruction, Communication and Denomination - Martin, Mary Clare (Studies in church history, 2019)
Catechizing played an important part in domestic religious education in Britain in the eighteenth and nineteenth centuries, as well as in the better documented early modern period. However, its significance has been neglected in comparison with family prayers (often deemed to be an expression of patriarchy), Sunday observance or even private prayers. This article analyses the incidence of catechizing across religious denominations in Britain from 1740 to 1870, and within selected overseas missionary families. Drawing on a wide range of personal memoirs, the article analyses the range of contexts and relationships within which catechizing could occur. These included not only household worship (which could be conducted by women) but also relationships between siblings. It demonstrates that catechizing could provide opportunities for asking questions and spending ‘quality time’ with parents and / or children, rather than embodying an alienating form of rote-learning. The article therefore challenges many stereotypes relating to family domestic education, relating to themes such as patriarchy, denominational difference and adult-child interaction.